2017
DOI: 10.1073/pnas.1701083114
|View full text |Cite
|
Sign up to set email alerts
|

A promiscuous split intein with expanded protein engineering applications

Abstract: The protein trans-splicing (PTS) activity of naturally split inteins has found widespread use in chemical biology and biotechnology. However, currently used naturally split inteins suffer from an "extein dependence," whereby residues surrounding the splice junction strongly affect splicing efficiency, limiting the general applicability of many PTS-based methods. To address this, we describe a mechanism-guided protein engineering approach that imbues ultrafast DnaE split inteins with minimal extein dependence. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
119
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 114 publications
(130 citation statements)
references
References 37 publications
2
119
0
Order By: Relevance
“…In fact, many groups have repeatedly observed yields of 10% or less with ncAA incorporation into transporters 36 , ion channels [37][38][39] , and G protein-coupled receptors 40,41 . Although the generally low yields observed with tPTS likely restrict the approach to applications that do not require large amounts of protein, at least some of the above limitations can be addressed by engineering more promiscuous and efficient split inteins [10][11][12]42 or by adding affinity tags to promote split intein interactions 18 . Such improvements would allow the approach to be applied to a broader complement of target proteins.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, many groups have repeatedly observed yields of 10% or less with ncAA incorporation into transporters 36 , ion channels [37][38][39] , and G protein-coupled receptors 40,41 . Although the generally low yields observed with tPTS likely restrict the approach to applications that do not require large amounts of protein, at least some of the above limitations can be addressed by engineering more promiscuous and efficient split inteins [10][11][12]42 or by adding affinity tags to promote split intein interactions 18 . Such improvements would allow the approach to be applied to a broader complement of target proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Further characterization of their properties would make them available as orthogonal functional parts for regulation of serine integrase-based applications. More recently, mutations at residues within the GEP loop of the Npu DnaE split intein have been identified that affect the specificity, reaction rates, and tolerance to changes in the flanking residues 16,17 . Use of these intein variants with broader specificities would require minimum changes to the extein sequence of the target integrase, thereby reducing the potential risk of introducing deleterious mutations.…”
Section: Intein-mediated Assembly Of Integrase-rdf Fusion Recombinasementioning
confidence: 99%
“…In order to study the conformation of the Tm1 tail domain in the context of fully assembled intermediate filaments, we used a split-intein system to produce a segmentally labeled form of the intact Tm1 protein (19). The tail domain, including residues 373 to 441, was expressed 40 separately from the N-terminus of the protein (residues 1 to 372).…”
Section: Resultsmentioning
confidence: 99%